Long-term sequelae and management following anterior cruciate ligament injury. (15th October 2014) - Peck, Jeffrey
Abstract : This article discusses a case in which a patient who sustained an anterior cruciate ligament (ACL) injury returned with anterior knee pain in the same knee approximately 20 years later. He underwent reconstruction at the time of the injury and had a revision reconstruction performed 10 years later. The case highlights the long-term consequences of ACL injury and subsequent reconstruction for the knee joint, as this patient has developed anterior knee pain during his mid-40s. Additionally, non-operative management of knee osteoarthritis is discussed.